2021
DOI: 10.2166/aqua.2021.009
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent water supply systems and their resilience to COVID-19: IWA IWS SG survey

Abstract: There is limited information about the current state of intermittent water supply (IWS) systems at the global level. A survey was carried out by the Intermittent Water Supply Specialist Group of the International Water Association (IWA IWS SG) to better understand the current state of these systems and challenges that water companies may have faced under COVID-19 pandemic and to capture successful management strategies applied by water utilities. The survey consisted of three parts: (1) general information abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In contrast, first flush samples averaged an HPC concentration of 4.3 × 10 4 MPN/100 mL (4.3 ± 2.8 × 10 4 MPN/100 mL) and were significantly higher than concentrations from stable IWS (Kruskal–Wallis, p < 0.001) which averaged 70 ± 109 MPN/100 mL and ranged from 5 to 300 MPN/100 mL. Other studies have also found a deterioration of water quality during first flush events when supply is restarted regardless of the duration of the stoppage; 15–17,64–66 although differences in water quality between first flush and stable supply may not be significant in all cases. 16…”
Section: Resultsmentioning
confidence: 89%
“…In contrast, first flush samples averaged an HPC concentration of 4.3 × 10 4 MPN/100 mL (4.3 ± 2.8 × 10 4 MPN/100 mL) and were significantly higher than concentrations from stable IWS (Kruskal–Wallis, p < 0.001) which averaged 70 ± 109 MPN/100 mL and ranged from 5 to 300 MPN/100 mL. Other studies have also found a deterioration of water quality during first flush events when supply is restarted regardless of the duration of the stoppage; 15–17,64–66 although differences in water quality between first flush and stable supply may not be significant in all cases. 16…”
Section: Resultsmentioning
confidence: 89%
“…More often, consumers use potable water under restricted conditions where water rationing is implemented. Predominantly, access to safe drinking water is affected by poor financial reserves and inadequate infrastructure [ 5 , 7 ]. Rapid population growth, industrialization, and climate change threaten freshwater resources resulting in substantial water shortages.…”
Section: Introductionmentioning
confidence: 99%
“…Provision of such a service is mainly via two main methods, namely, the piped water distribution network and tanker-based water supply systems. To this end, challenges related to water supply in urban areas include (i) low reliability of piped distribution system supply , and (ii) lack of full coverage by the piped water distribution network in peri-urban areas . Piped water supply being spatially and temporally uneven across the city, tanker-based water supply is one of the most prominent forms of alternative arrangements for water distribution in cities of various countries like India, Italy, Malaysia, Kenya, etc. These tanker water distribution systems facilitate residents in peri-urban areas who are not connected to piped network infrastructure and also in urban areas where people are facing water shortages due to highly intermittent nature of piped distribution systems.…”
Section: Introductionmentioning
confidence: 99%